2013
DOI: 10.1007/s10802-013-9757-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Adolescent Rumination and its Association with Depressive Symptoms

Abstract: Rumination is an important cognitive vulnerability for adolescent and adult depression. However, little is known about the aetiological origins of rumination, as well as its association with depression. Adolescent rumination (self-report) and depressive symptoms (self- and parent-report) were assessed in 674 pairs of same-gender Chinese adolescent twins (11-17 years of age). Females accounted for 53.7 % of the sample. There were significant correlations between self-reported rumination and self-reported depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 71 publications
7
17
0
3
Order By: Relevance
“…Our results that rumination is moderately heritable in adulthood extend those from prior research (Chen & Li, 2013; Moore et al, 2013) in two ways. First, we examined multiple measures of rumination, including a latent variable, so we are confident that our results extend beyond a specific measure of rumination.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results that rumination is moderately heritable in adulthood extend those from prior research (Chen & Li, 2013; Moore et al, 2013) in two ways. First, we examined multiple measures of rumination, including a latent variable, so we are confident that our results extend beyond a specific measure of rumination.…”
Section: Discussionsupporting
confidence: 84%
“…Moore et al (2013) examined 12–14-year-old twins and found that rumination and depressive symptoms were both heritable ( h 2 =.17 and .54, respectively), and that their association was largely genetic (genetic correlation[ rA ]=.83). These findings were supported by a study of Chinese twins ages 11–17 (Chen & Li, 2013), which found a low heritability for rumination ( h 2 =.24) and substantial genetic overlap between rumination and depressive symptoms ( rA =.99).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Notably, this study is the first to provide evidence that the link between maternal depression and brooding rumination is moderated by genetic influences and add to the growing body of research suggesting that rumination may be an important endophenotype for depression risk (see also Chen & Li, 2013; Johnson et al, 2014; Moore et al, 2013). Furthermore, these findings provide initial evidence that biological stress reactivity (via HPA axis disruption) is a plausible mechanism underlying the link between maternal depression and children’s brooding.…”
Section: Discussionmentioning
confidence: 74%
“…As noted earlier, it is associated with depression concurrently (for reviews, see Abela & Hankin, 2008; Rood et al, 2009) and prospectively predicts onset of the disorder (Abela & Hankin, 2011; Gibb et al, 2012). Research also suggests that rumination is moderately heritable ( h 2 = .20–.41) and exhibits shared genetic variability with depression (Chen & Li, 2013; Johnson et al, 2014; Moore et al, 2013), supporting its potential role as an endophenotype. A key question then is whether high levels of brooding rumination will be observed in an at-risk population such as children of depressed mothers, whether this relation is moderated by specific genetic influences such as CRHR1 , and whether the effects are at least partially independent of children’s own current or past depression.…”
mentioning
confidence: 92%